How to Build a Life in the Humanities - Grafton, Anthony. author. aut Link
XVIII, 245 p.
Keywords: A follow-up to the popular Graduate Study for the 21st Century , this book seeks to expand professional development to include the personal aspects of daily lives in the humanities. How to Build a Life in the Humanities delves into pressing work-life issues such as post-tenure depression, academic life with children, aging, and adjuncting.